I knew her well - Piccioni, Piero 1921-2004 (The Criterion collection, 2016)
"Following the gorgeous, seemingly liberated Adriana as she chases her dreams in the Rome of "La dolce vita", "I Knew Her Well" is at once a delightful immersion in the popular music and style of Italy in the sixties and a biting critique of its sexual politics and the culture of celebrity. Over a series of intimate episodes, just about every one featuring a different man, a new hairstyle, and an outfit to match, the unsung Italian master Antonio Pietrangeli, working from a script he cowrote with Ettore Scola, composes a deft, seriocomic character study that never strays from its complicated central figure. "I Knew Her Well" is a thrilling rediscovery, by turns funny, tragic, and altogether jaw-dropping." [criterion.com]
Original: Italien, Frankreich, Deutschland 1965
Bildformat 1.85:1
DVD special edition features: new 4K digital restoration ; new interview with actor Stefania Sandrelli ; new interview with film scholar Luca Barattoni about the career of director Antonio Pietrangeli ; archival footage of Sandrelli's audition ; trailer ; new english subtitle translation ; plus: an essay by journalist and author Alexander Stille
Keywords: Geliebter; Suizid; Junge Frau; Rom; Film; DVD-Video